Influences of social media marketing on pre-adult consumers - Filipe, Sandra
This paper reports on the use of social media marketing by pre-adults, setting off from a case study of students of different courses at one Portuguese higher education school. Data were collected through a questionnaire available online and analysed with descriptive statistical techniques. Based on the pointed outlines, this research explores and analyses four key issues: (1) what are the types of social media that students are using?; (2) in which contexts are they using each social media type?; (3) what are their opinions about the persuasive intentions of social media marketing?; and (4) how does social media marketing influence their brand knowledge, attitude and behaviour?. Within the research questions proposed, the study points towards some understanding of how the young at this age and education level see social media marketing. Furthermore, in this paper, tendencies around the concepts, the tools and levels of attraction by the audiences, with focus on relationship marketing in the 2.0 era, are revisited. This study, by focusing on this age group, contributes with critical information that might help cast light over recent theories and practices of social media marketing. The main results show that the youngsters are fans of several brands, although they do not follow them continuously, or follow only a few of those in which they are more interested, also show that the youngsters consider the use of social media for dissemination and promotion of brands and products useful, although some have indicated that sometimes they feel that their privacy is invaded.